Method for rapidly synthesizing silicate positive electrode material and application thereof
Through the rapid thermal shock treatment method, the problems of slow kinetics of ferromagnesium silicate positive electrode materials in olivine structure and high cost and high energy consumption of solid-phase sintering process are solved, and the efficient preparation and excellent electrochemical performance of silicate positive electrode materials are achieved.
Patent Information
- Application Number
- CN202411820329.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
The olivine structure ferromagnesium silicate positive electrode material has slow kinetics due to its low intrinsic electron and ionic conductivity, and the solid-phase sintering process is high cost and energy consumption, which limits its wide application in the battery field.
By using the rapid thermal shock treatment method, the raw materials are mechanically activated and dried and secondary sintered to prepare a silicate positive electrode material with excellent electrochemical properties.
It significantly improves the cyclic stability and electrochemical performance of silicate cathode materials, reduces production costs and energy consumption, and is suitable for large-scale industrial production.
Smart Images

Figure CN119612529A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesium ion batteries, and in particular to a method for rapidly synthesizing a silicate positive electrode material and an application thereof. Background Art
[0002] With the rapid development of modern science and technology, the demand for efficient, environmentally friendly and cost-controlled battery materials is growing. Olivine-structured magnesium iron silicate cathode materials stand out among many battery materials due to their significant advantages such as stable voltage platform, relatively low manufacturing cost, abundant raw material sources on the earth and excellent environmental friendliness, and have attracted extensive attention and in-depth research from researchers.
[0003] However, the structural characteristics of the olivine-structured magnesium iron silicate cathode material itself also bring some significant problems. Its intrinsic electronic and ionic conductivity is low, resulting in slow kinetics during the charge and discharge process. In practical applications, it is reflected in the poor charge and discharge rate performance, the inability to quickly complete charge and discharge at high current density, and it is difficult to adapt to the needs of high-power equipment; and after long-term cycling, the capacity decays significantly, and the battery life is greatly shortened, which seriously hinders its wider commercial application and further expansion in the battery field.
[0004] At present, solid-phase sintering is widely used in the industry to coat and dope magnesium iron silicate positive electrode materials to improve their electrochemical performance. Solid-phase sintering requires long-term heat preservation in a high-temperature environment to achieve the densification of the material. In this process, not only a large amount of energy is consumed, which significantly increases production costs, but also more stringent requirements are placed on the high-temperature resistance of the equipment. In view of this situation, it is extremely urgent and important to develop a method that can quickly synthesize magnesium iron silicate positive electrode materials, which is of great significance for promoting the further application and development of this material in the battery field. Summary of the invention
[0005] The present invention aims to provide a method for rapidly synthesizing silicate cathode materials and their application, so as to effectively solve the problems of slow kinetics caused by low intrinsic conductivity of existing olivine structure magnesium iron silicate cathode materials and high cost and high energy consumption caused by solid phase sintering process.
[0006] To achieve the above object, the present invention adopts the following technical solution: a method for rapidly synthesizing silicate positive electrode materials, comprising the following steps:
[0007] S1: Mechanically activate the magnesium source, iron source, silicon source and manganese source in a certain proportion and mix them evenly to obtain a mixed precursor;
[0008] S2: drying the mixed precursor obtained in S1;
[0009] S3: placing the dried mixed precursor on a heating base of a heating device, and performing a rapid thermal shock treatment under a protective atmosphere to obtain a silicate positive electrode material.
[0010] Preferably, in S1, the molar ratio of magnesium source, iron source, silicon source and manganese source is 1:(1-x):1:x, wherein 0.01 <x≤1。
[0011] Preferably, in S2, in S3, the rapid thermal shock treatment process comprises the following steps:
[0012] S3.1: Adjust the current of the heating device, quickly raise the temperature to 300-450℃, and keep it for 20-90S for pre-sintering;
[0013] S3.2: Continue to adjust the current of the heating device to quickly raise the temperature to 850-1000°C, and keep the temperature for 10-30s for secondary sintering.
[0014] Preferably, in S3.1 and S3.2, the heating rate is 10 3 -10 5 ℃ / s.
[0015] Preferably, in S3, the heating substrate is any one of carbon cloth, carbon paper, carbon felt, nickel foil, and stainless steel foil.
[0016] Preferably, in S2, the drying temperature is 80-120°C and the drying time is 8-12h.
[0017] Preferably, the magnesium source is any one of magnesium oxide, magnesium carbonate, magnesium nitrate and magnesium acetate; the iron source is any one of ferrous oxalate, ferrous acetate and ferrous sulfate; the silicon source is nano-silicon dioxide; and the manganese source is any one of manganese carbonate, magnesium acetate and manganese nitrate.
[0018] Preferably, the heating device is a Joule ultrafast heating device.
[0019] Preferably, in S1, the mechanical activation method is ball milling mixing, and the mechanical activation time is 6-18 hours.
[0020] The present invention also provides another technical solution, which is an application of a rapid synthesis of silicate positive electrode materials. The synthesized silicate positive electrode material is applied to magnesium ion batteries.
[0021] Compared with the prior art, the beneficial effects of this solution are:
[0022] The rapid thermal shock treatment method adopted by the present invention is based on the Joule heating principle. During the sintering process, when a high current passes through the material, heat is generated due to the material's own resistance, thereby achieving extremely fast heating and cooling rates. This rapid thermal cycle greatly shortens the production cycle of silicate positive electrode materials and significantly improves production efficiency. Compared with traditional processes, energy consumption can be greatly reduced, thereby effectively reducing production costs, which makes this technology highly feasible and competitive in industrial large-scale production.
[0023] Compared with the existing solid-phase sintering technology, the rapid thermal shock treatment of this technical solution has outstanding environmentally friendly characteristics, and basically no pollution is generated during the entire treatment process. From the perspective of improving material performance, it can significantly optimize the cycle stability and electrochemical performance of silicate positive electrode materials. Specifically, the silicate positive electrode material prepared by this scheme effectively overcomes the problem of slow kinetics caused by the low intrinsic conductivity of the existing olivine structure magnesium iron silicate positive electrode material, while also avoiding the high cost and high energy consumption disadvantages brought about by the solid-phase sintering process. For example, at a current density of 0.5C, the first discharge specific capacity of the material of this scheme is as high as 753.25mAh / g. After about 50 cycles of activation, the capacity tends to be stable. After 250 cycles, it can still retain more than 95% of the capacity, and the discharge specific capacity is 192.82mAh / g. In comparison, the existing silicate cathode materials prepared by solid phase sintering have larger particle sizes, mainly in the range of 250-400nm. At the same 0.5C current density, the initial discharge capacity is only 427.78mAh / g. Although the capacity tends to be stable after about 50 cycles, the discharge capacity after 250 cycles is only 164.1mAh / g. The data comparison clearly shows that the scheme of the present invention has excellent advantages in both material performance improvement and cost control, and provides strong technical support for the further development and wide application of olivine structure magnesium iron silicate cathode materials in the battery field. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The silicate positive electrode material MgFe synthesized in Example 1 of the present invention 0.5 Mn 0.5 X-ray diffraction spectra, microscopic morphology, particle size statistics and element distribution of SiO4;
[0025] Figure 2 The silicate positive electrode material MgFe synthesized in Example 1 of the present invention 0.5 Mn 0.5 Cycle curve of magnesium ion battery after SiO4 is assembled as positive electrode material;
[0026] Figure 3 The silicate positive electrode material MgFe synthesized in Example 2 of the present invention0.7 Mn 0.3 X-ray diffraction spectra, microscopic morphology, particle size statistics and element distribution of SiO4;
[0027] Figure 4 A cycle curve diagram of a magnesium ion battery assembled with a fast synthesized silicate positive electrode material (MgFe0.7Mn0.3SiO4) prepared in an embodiment of the present invention as a positive electrode material;
[0028] Figure 5 The silicate positive electrode material MgFe synthesized in Example 2 of the present invention 0.7 Mn 0.3 X-ray diffraction spectra, microscopic morphology, particle size statistics and element distribution of SiO4;
[0029] Figure 6 The silicate positive electrode material MgFe synthesized in Example 3 of the present invention 0.9 Mn 0.1 Cycle curve of magnesium ion battery after SiO4 is assembled as positive electrode material;
[0030] Figure 7 The silicate positive electrode material MgFe synthesized in Comparative Example 1 of the present invention 0.7 Mn 0.3 X-ray diffraction spectra, microscopic morphology, particle size statistics and element distribution of SiO4-F;
[0031] Figure 8 The silicate positive electrode material MgFe synthesized in Comparative Example 1 of the present invention 0.7 Mn 0.3 Cycling curve of magnesium-ion battery after SiO4-F is assembled as positive electrode material;
[0032] Fig. 9 (a) is the silicate positive electrode material MgFe synthesized in Comparative Example 2 of the present invention 0.7 Mn 0.3 X-ray diffraction spectrum of SiO4-primary sintering;
[0033] like Fig. 9 (b) is the silicate positive electrode material MgFe synthesized in Comparative Example 2 of the present invention 0.7 Mn 0.3 SiO4-cycle curve of primary sintering;
[0034] Fig.10 (a) is an X-ray diffraction spectrum of the silicate positive electrode material MgFeSiO4 synthesized in Comparative Example 3 of the present invention;
[0035] like Fig.10(b) Cyclic voltammetry curve of the silicate cathode material MgFeSiO4 synthesized in Comparative Example 3 of the present invention;
[0036] Fig.11 (a) X-ray diffraction spectrum of the silicate cathode material MgFe 0.99 Mn 0.01 SiO4 synthesized in Comparative Example 4 of the present invention;
[0037] As Fig.11 (b) Cyclic voltammetry curve of the silicate cathode material MgFe 0.99 Mn 0.01 SiO4 synthesized in Comparative Example 4 of the present invention. Detailed implementation manners
[0038] The following is a further detailed description through specific implementation manners:
[0039] Example 1
[0040] A method for rapidly synthesizing a silicate cathode material, comprising the following steps:
[0041] S1: Mechanically activate a magnesium source, an iron source, a silicon source, and a manganese source in a certain ratio, and mix them evenly to obtain a uniformly mixed precursor;
[0042] Among them, the molar ratios of the magnesium source, the iron source, silicon, and the manganese source are 1:(1 - x):1:x (0.01 < x ≤ 1) in sequence. The magnesium source is any one of magnesium oxide, magnesium carbonate, magnesium nitrate, and magnesium acetate; the iron source is any one of ferrous oxalate, ferrous acetate, and ferrous sulfate; the silicon source is nano-silica; the manganese source is any one of manganese carbonate, magnesium acetate, and manganese nitrate; the mechanical activation method is ball milling and mixing, and the mechanical activation time is 6 - 18 h. In this example, magnesium oxide, ferrous oxalate, nano-silica, and manganese carbonate are weighed respectively according to the molar ratio of 1:0.5:
[0043] 1:0.5, and then mixed by ball milling. During the ball milling process, the ball-to-material ratio is controlled to be 20:3, and mechanically activated for 12 h to make the raw materials mixed evenly to obtain a uniformly mixed precursor;
[0044] S2: Perform a drying treatment on the uniformly mixed precursor obtained in S1. The drying temperature is 80 - 120 °C, and the drying time is 8 - 12 h. In this example, the drying temperature is 100 °C, and the drying time is 12 h;
[0045] S3: placing the dried mixed precursor on a heating substrate of a heating device, and performing a rapid thermal shock treatment under a protective atmosphere to obtain a silicate positive electrode material, wherein the heating substrate is any one of carbon cloth, carbon paper, carbon felt, nickel foil, and stainless steel foil; in this embodiment, the heating device is a Joule ultrafast heating device; the protective atmosphere is nitrogen; and the heating substrate is carbon cloth;
[0046] The rapid thermal shock treatment process includes the following steps:
[0047] S3.1: Adjust the current of the heating device, quickly raise the temperature to 300-450℃, keep the temperature for 20-90S for pre-sintering, and the heating rate is 10 3 -10 5 ℃ / s; In this embodiment, the temperature is quickly raised to 350℃ and kept for 60S for pre-sintering, and the heating rate is 10 3 °C / s;
[0048] S3.2: Continue to adjust the current of the heating device to quickly raise the temperature to 850-1000℃, keep it warm for 10-30s for secondary sintering, and the heating rate is 10 3 -10 5 ℃ / s, to obtain silicate positive electrode material MgFe 0.5 Mn 0.5 In this embodiment, the temperature is quickly raised to 900 ° C, kept for 30s for secondary sintering, and the heating rate is 10 3 ℃ / s.
[0049] The invention discloses an application of rapidly synthesizing silicate positive electrode materials, wherein the synthesized silicate positive electrode materials are applied in magnesium ion batteries.
[0050] The silicate positive electrode material MgFe synthesized in Example 1 0.5 Mn 0.5 SiO4 was tested by X-ray diffraction spectrum, and the test results were as follows Figure 1 As shown in (a), the synthesized silicate positive electrode material MgFe 0.5 Mn 0.5 The main characteristic peaks of SiO4 can match well with the standard card of MgFeSiO4 crystal phase (JCPDS: 76-0853), but the main strong peak is slightly offset, indicating that the silicate positive electrode material MgFe can be synthesized under this condition. 0.5 Mn 0.5 SiO4.
[0051] The silicate positive electrode material MgFe synthesized in Example 1 0.5 Mn 0.5 SiO4 was subjected to microscopic morphology analysis, and the results were as follows Figure 1(b) and 1(c), it can be seen from the figure that the synthesized silicate positive electrode material MgFe 0.5 Mn 0.5 The particle size of SiO4 is mainly in the range of 20-40nm. Smaller nanoparticles have a larger specific surface area, which increases the contact area between the material and the electrolyte. Smaller nanoparticles can shorten the diffusion path of magnesium ions in the material, which helps to improve the electrochemical performance.
[0052] The silicate cathode material MgFe synthesized in Example 1 was analyzed by EDS-Mapping. 0.5 Mn 0.5 SiO4 was characterized and the results were as follows Figure 1 As shown in (d), the synthesized silicate positive electrode material MgFe 0.5 Mn 0.5 The uniform distribution of Mg, Fe, Mn, Si and O in SiO4 further illustrates that the silicate cathode material MgFe 0.5 Mn 0.5 SiO4 was successfully synthesized.
[0053] The silicate positive electrode material MgFe synthesized in Example 1 0.5 Mn 0.5 SiO4 was used as the positive electrode material of the magnesium ion battery, magnesium foil was used as the negative electrode of the magnesium ion battery, 0.5M Mg(TFSI)2 / MgCl2 / DME was selected as the electrolyte, GF / A was selected as the separator, and the magnesium ion battery was assembled. The test was carried out at a current density of 0.5C. The test results are as follows Figure 2 As shown, at a current density of 0.5C, the initial discharge specific capacity is 373.18 mAh / g. After about 50 cycles of activation, the capacity tends to be stable, and after 250 cycles, the capacity can be retained by more than 95%, and its discharge specific capacity is 152.59 mAh / g.
[0054] Example 2
[0055] Different from Example 1, a method for rapidly synthesizing a silicate positive electrode material is as follows: in S1, magnesium oxide, ferrous oxalate, nano-silicon dioxide and manganese carbonate are weighed in a molar ratio of 1:0.7:1:0.3; in S3, a silicate positive electrode material MgFe is prepared. 0.7 Mn 0.3 SiO4.
[0056] The silicate positive electrode material MgFe synthesized in Example 2 0.7 Mn 0.3 SiO4 was tested by X-ray diffraction spectrum, and the test results were as follows Figure 3 As shown in (a), the synthesized silicate positive electrode material MgFe 0.7 Mn0.3 The main characteristic peaks of SiO4 can match well with the standard card of MgFeSiO4 crystal phase (JCPDS: 76-0853), but the main strong peak is slightly offset, indicating that the silicate positive electrode material MgFe can be synthesized under this condition. 0.7 Mn 0.3 SiO4.
[0057] The silicate positive electrode material MgFe synthesized in Example 2 0.7 Mn 0.3 SiO4 was subjected to microscopic morphology analysis, and the results were as follows Figure 3 (b) and 3(c), it can be seen from the figure that the synthesized silicate positive electrode material MgFe 0.7 Mn 0.3 The particle size of SiO4 is mainly in the range of 10-30 nm. Compared with the silicate positive electrode material synthesized in Example 1, the particle size of the silicate positive electrode material synthesized in Example 2 is smaller, which is more conducive to improving the electrochemical performance.
[0058] The silicate cathode material MgFe synthesized in Example 2 was analyzed by EDS-Mapping. 0.7 Mn 0.3 SiO4 was characterized and the results were as follows Figure 3 As shown in (d), the synthesized silicate positive electrode material MgFe 0.7 Mn 0.3 The uniform distribution of Mg, Fe, Mn, Si and O in SiO4 further illustrates that the silicate cathode material MgFe 0.7 Mn 0.3 SiO4 was successfully synthesized.
[0059] The silicate positive electrode material MgFe synthesized in Example 2 0.7 Mn 0.3 SiO4 was used as the positive electrode material of the magnesium ion battery, and the magnesium ion battery was assembled in the same manner as in Example 1, which will not be described in detail here. The test was carried out at a current density of 0.5C, and the test results are shown in FIG. Figure 4 As shown, at a current density of 0.5C, the initial discharge specific capacity is 753.25 mAh / g. After about 50 cycles of activation, the capacity tends to be stable, and after 250 cycles, the capacity can be retained by more than 95%, and its discharge specific capacity is 192.82 mAh / g.
[0060] Example 3
[0061] Different from Example 1, a method for rapidly synthesizing a silicate positive electrode material is as follows: in S1, magnesium oxide, ferrous oxalate, nano-silicon dioxide and manganese carbonate are weighed in a molar ratio of 1:0.9:1:0.1; in S3, a silicate positive electrode material MgFe0.9 Mn 0.1 SiO4.
[0062] The silicate positive electrode material MgFe synthesized in Example 3 0.9 Mn 0.1 SiO4 was tested by X-ray diffraction spectrum, and the test results were as follows Figure 5 As shown in (a), the synthesized silicate positive electrode material MgFe 0.9 Mn 0.1 The main characteristic peaks of SiO4 can match well with the standard card of MgFeSiO4 crystal phase (JCPDS: 76-0853), but the main strong peak is slightly offset, indicating that the silicate positive electrode material MgFe can be synthesized under this condition. 0.9 Mn 0.1 SiO4.
[0063] The silicate positive electrode material MgFe synthesized in Example 3 0.9 Mn 0.1 SiO4 was subjected to microscopic morphology analysis, and the results were as follows Figure 5 (b) and 5(c), it can be seen from the figure that the synthesized silicate positive electrode material MgFe 0.9 Mn 0.1 The particle size of SiO4 is mainly in the range of 70-90nm.
[0064] The silicate cathode material MgFe synthesized in Example 3 was analyzed by EDS-Mapping. 0.9 Mn 0.1 SiO4 was characterized and the results were as follows Figure 5 As shown in (d), the synthesized silicate positive electrode material MgFe 0.9 Mn 0.1 The uniform distribution of Mg, Fe, Mn, Si and O in SiO4 further illustrates that the silicate cathode material MgFe 0.9 Mn 0.1 SiO4 was successfully synthesized.
[0065] The silicate positive electrode material MgFe synthesized in Example 3 0.9 Mn 0.1 SiO4 was used as the positive electrode material of the magnesium ion battery, and the magnesium ion battery was assembled in the same manner as in Example 1, which will not be described in detail here. The test was carried out at a current density of 0.5C, and the test results are shown in FIG. Figure 4 As shown, at a current density of 0.5C, the initial discharge specific capacity is 711.04 mAh / g. After about 50 cycles of activation, the capacity tends to be stable, and after 250 cycles, the capacity can be retained by more than 95%, and its discharge specific capacity is 170.02 mAh / g.
[0066] Comparative Example 1
[0067] Different from Example 2, in S3, the dried mixed precursor is placed in a tubular furnace filled with a protective atmosphere for two high-temperature sinterings. First, the temperature is raised to 350°C for sintering for 2 hours, and then the temperature is raised to 900°C for 6 hours. The heating rate of the entire sintering process is 2°C / min, and finally the silicate positive electrode material MgFe 0.7 Mn 0.3 SiO4-F.
[0068] Comparative Example 1 Synthesized Silicate Positive Electrode Material MgFe 0.7 Mn 0.3 SiO4-F was tested by X-ray diffraction spectrum, and the test results were as follows Figure 7 As shown in (a), the synthesized silicate positive electrode material MgFe 0.7 Mn 0.3 The main characteristic peaks of SiO4-F can match well with the standard card of MgFeSiO4 crystal phase (JCPDS: 76-0853), but the main strong peak is slightly offset, indicating that the silicate positive electrode material MgFe can be synthesized under this condition. 0.7 Mn 0.3 SiO4-F.
[0069] Comparative Example 1 Synthesized Silicate Positive Electrode Material MgFe 0.7 Mn 0.3 SiO4-F was subjected to microscopic morphology analysis. The results are as follows Figure 7 (b) and 7(c), it can be seen from the figure that the synthesized silicate positive electrode material MgFe 0.7 Mn 0.3 The particle size of SiO4-F is mainly in the range of 250-400 nm. It can be seen that the particle size of the silicate positive electrode material synthesized by the scheme of Comparative Example 1 is very large, which is not conducive to improving the electrochemical performance.
[0070] The silicate positive electrode material MgFe synthesized in Comparative Example 1 was compared by EDS-Mapping. 0.7 Mn 0.3 SiO4-F was characterized and the results were as follows Figure 7 As shown in (d), the synthesized silicate positive electrode material MgFe 0.7 Mn 0.3 The uniform distribution of Mg, Fe, Mn, Si and O in SiO4-F further illustrates that the silicate cathode material MgFe 0.7 Mn 0.3 SiO4-F was successfully synthesized.
[0071] The silicate positive electrode material MgFe 0.7Mn 0.3 SiO4-F was used as the positive electrode material of the magnesium ion battery. The magnesium ion battery was assembled in the same manner as in Example 1 and will not be described in detail here. The test was conducted at a current density of 0.5C. The test results are shown in FIG. Figure 8 As shown, at a current density of 0.5C, the initial discharge capacity is 427.78 mAh / g. After about 50 cycles of activation, the capacity tends to be stable, and after 250 cycles, the discharge capacity is 164.1 mAh / g.
[0072] Comparative Example 2
[0073] Different from Example 2, in a method for rapidly synthesizing silicate positive electrode materials, in S3, the rapid thermal shock treatment process is as follows: adjusting the current of the heating device, rapidly heating to 900°C, keeping the temperature for 30s for sintering, and heating at a rate of 10 3 ℃ / s, to obtain silicate positive electrode material MgFe 0.7 Mn 0.3 SiO4-sintered once.
[0074] Comparative Example 2 Synthesized Silicate Positive Electrode Material MgFe 0.7 Mn 0.3 SiO4-sintered once and tested by X-ray diffraction spectrum, the test results are as follows Fig. 9 As shown in (a), the synthesized silicate positive electrode material MgFe 0.7 Mn 0.3 The main characteristic peaks of SiO4-primary sintering can match well with the standard card of MgFeSiO4 crystal phase (JCPDS: 76-0853), and the main strong peak has a slight shift, indicating that the silicate positive electrode material MgFe can be synthesized under this condition. 0.7 Mn 0.3 SiO4-sintered once.
[0075] The silicate positive electrode material MgFe synthesized in Comparative Example 2 0.7 Mn 0.3 SiO4- was used as the positive electrode material of the magnesium ion battery in the first sintering process. The magnesium ion battery was assembled in the same manner as in Example 1 and will not be described in detail here. The test was conducted at a current density of 0.5C. The test results are shown in FIG. Fig. 9 As shown in (b), at a current density of 0.5C, the initial discharge capacity is 361.8 mAh / g, and after 250 cycles, the discharge capacity is 136.7 mAh / g.
[0076] Comparative Example 3
[0077] Different from Example 2, a method for quickly synthesizing a silicate positive electrode material is provided. In S1, magnesium oxide, ferrous oxalate and nano-silicon dioxide are weighed respectively in a molar ratio of 1:1:1, and then mixed by ball milling. During the ball milling process, the ball-to-material ratio is controlled to be 20:3, and mechanical activation is performed for 12 hours to mix the raw materials evenly to obtain a mixed precursor. In S3, the silicate positive electrode material MgFeSiO4 is obtained.
[0078] The silicate positive electrode material MgFeSiO4 synthesized in Comparative Example 3 was tested by X-ray diffraction spectrum. The test results are as follows: Fig.10 As shown in (a), it can be seen from the figure that the main characteristic peaks of the synthesized silicate positive electrode material MgFeSiO4 can match well with the standard card of MgFeSiO4 crystal phase (JCPDS: 76-0853), indicating that the silicate positive electrode material MgFeSiO4 can be synthesized under this condition.
[0079] The silicate positive electrode material MgFeSiO4 synthesized in Comparative Example 3 was used as the positive electrode material of the magnesium ion battery to assemble the magnesium ion battery. The assembly method was the same as that of Example 1 and will not be described in detail here. The test was carried out at a current density of 1C. The test results are shown in FIG. Fig.10 As shown in (b), at a current density of 1C, the initial discharge capacity is 97 mAh / g, and after 250 cycles, the discharge capacity is 89 mAh / g.
[0080] Comparative Example 4
[0081] Different from Example 2, a method for rapidly synthesizing a silicate cathode material is provided. In S1, magnesium oxide, ferrous oxalate, nano-silicon dioxide and manganese carbonate are weighed in a molar ratio of 1:0.99:1:0.01, and then mixed by ball milling. During the ball milling process, the ball-to-material ratio is controlled to be 20:3, and mechanical activation is performed for 12 hours to uniformly mix the raw materials to obtain a mixed precursor. In S3, a silicate cathode material MgFe 0.99 Mn 0.01 SiO4.
[0082] Comparative Example 4 Synthesized Silicate Positive Electrode Material MgFe 0.99 Mn 0.01 SiO4 was tested by X-ray diffraction spectrum, and the test results were as follows Fig.11 As shown in (a), the synthesized silicate positive electrode material MgFe 0.99 Mn 0.01 The main characteristic peaks of SiO4 can match well with the standard card of MgFeSiO4 crystal phase (JCPDS: 76-0853), but the main strong peak is slightly offset, indicating that the silicate positive electrode material MgFe can be synthesized under this condition. 0.99 Mn 0.01SiO4.
[0083] The silicate positive electrode material MgFe synthesized in Comparative Example 4 0.99 Mn 0.01 SiO4 was used as the positive electrode material of the magnesium ion battery. The magnesium ion battery was assembled in the same manner as in Example 1 and will not be described in detail here. The test was conducted at a current density of 1C. The test results are shown in FIG. Fig.11 As shown in (b), at a current density of 1C, the initial discharge capacity is 368.2 mAh / g, and after 250 cycles, the discharge capacity is 66 mAh / g.
[0084] In summary, through the experimental results of Examples 1-3, the electrochemical performance of the materials synthesized by the rapid synthesis method is improved with the increase of manganese content; when the doping amount of manganese is 0.3, it has relatively excellent electrochemical cycle performance; as the doping amount increases to 0.5, the electrochemical performance is slightly reduced. And the different manganese content makes the morphology and size of the materials slightly different.
[0085] By comparing Comparative Example 1 with Example 2, it is found that the use of rapid thermal shock treatment for sintering can significantly improve the electrochemical performance of the material. 0.7 Mn 0.3 The particle size of SiO4-F is mainly in the range of 250-400nm, while the MgFe 0.7 Mn 0.3 The particle size of SiO4 material is 10-30nm. This is mainly due to the fact that the rapid thermal shock synthesis method is different from the slow and continuous heating and cooling process of the tube furnace. When the solid raw material is heated, the entire high-temperature superconducting process lasts within milliseconds, the reaction temperature can instantly reach 3000K or even higher, and the heating and cooling rates can be as high as 10 3 -10 5 / s, thus achieving materials with finer morphology particles. 0.7 Mn 0.3 SiO4 material has excellent cycle stability when used as the positive electrode material of magnesium ion batteries.
[0086] By comparing Comparative Example 2 with Example 2, it is found that the same raw material is directly sintered at the same temperature and time as the secondary sintering conditions in Example 2 by rapid thermal shock treatment to prepare MgFe 0.7 Mn 0.3 SiO4-primary sintered material. 0.7 Mn 0.3The physical phase of SiO4-single sintered material can also match the standard card, but its discharge specific capacity test result is significantly lower than the specific capacity of the material in Example 2. This result shows that the preparation method through double sintering has better cycle stability.
[0087] By comparing Comparative Example 3 with Example 2, it is found that the physical performance of Comparative Example 3 and Example 2, using the same rapid thermal shock method to synthesize the material, matches the standard card, but the main peak of Example 2 is slightly offset, indicating that the manganese element is successfully doped. However, the discharge specific capacity test result of Comparative Example 3 is significantly lower than that of Example 2, indicating that the doping of manganese can effectively improve the electrochemical cycle performance of the material.
[0088] By comparing Comparative Example 4 with Example 2, it is found that the physical performance of Comparative Example 4 and Example 2 matches the standard card, and when the doping amount is low, the main peak shift phenomenon is relatively less obvious. And by comparing their corresponding electrochemical properties, it can be seen that the material with a low manganese doping amount cannot improve its electrochemical cycle performance very well.
[0089] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for rapidly synthesizing a silicate positive electrode material, characterized in that: The following steps are involved: S1: Mechanically activate the magnesium source, iron source, silicon source and manganese source in a certain proportion and mix them evenly to obtain a mixed precursor; S2: drying the mixed precursor obtained in S1; S3: placing the dried mixed precursor on a heating base of a heating device, and performing a rapid thermal shock treatment under a protective atmosphere to obtain a silicate positive electrode material.
2. The method for rapidly synthesizing silicate positive electrode materials according to claim 1, characterized in that: In S1, the molar ratios of magnesium source, iron source, silicon source and manganese source are 1:(1-x):1:x, where 0.01 <x≤1。 3. A method for rapidly synthesizing silicate positive electrode materials according to claim 2, characterized in that: In S3, the rapid thermal shock treatment process comprises the following steps: S3.1: Adjust the current of the heating device, quickly raise the temperature to 300-450℃, and keep it for 20-90S for pre-sintering; S3.2: Continue to adjust the current of the heating device to quickly raise the temperature to 850-1000°C, and keep the temperature for 10-30s for secondary sintering.
4. The method for rapidly synthesizing silicate positive electrode materials according to claim 3, characterized in that: In S3.1 and S3.2, the heating rate is 10 3 -10 5 ℃ / s.
5. The method for rapidly synthesizing silicate positive electrode materials according to claim 4, characterized in that: In S3, the heating substrate is any one of carbon cloth, carbon paper, carbon felt, nickel foil, and stainless steel foil.
6. The method for rapidly synthesizing silicate positive electrode materials according to claim 5, characterized in that: In S2, the drying temperature is 80-120°C and the drying time is 8-12h.
7. A method for rapidly synthesizing silicate positive electrode materials according to claim 6, characterized in that: The magnesium source is any one of magnesium oxide, magnesium carbonate, magnesium nitrate and magnesium acetate; the iron source is any one of ferrous oxalate, ferrous acetate and ferrous sulfate; the silicon source is nano silicon dioxide; and the manganese source is any one of manganese carbonate, magnesium acetate and manganese nitrate.
8. The method for rapidly synthesizing silicate positive electrode materials according to claim 7, characterized in that: In S3, the heating device adopts a Joule ultrafast heating device.
9. A method for rapidly synthesizing silicate positive electrode materials according to claim 8, characterized in that: In S1, the mechanical activation method is ball milling mixing, and the mechanical activation time is 6-18h.
10. An application of rapid synthesis of silicate positive electrode materials, characterized in that: The silicate positive electrode material synthesized according to claims 1-9 is used in magnesium ion batteries.
Citation Information
Patent Citations
Magnesium ion battery positive electrode material, and preparation method and application thereof
CN109659536A
Preparation method and application of silicate positive electrode material MgFeSiO4
CN117776192A
Method for preparing low-temperature high-magnetic-induction oriented silicon steel through rapid heating, decarburization and annealing
CN117987630A
Silicate compound, positive electrode for secondary battery, and method for producing secondary battery
JP2013067543A
Fabrication method of graphene film by using joule heating
KR1020110020444A